Learn Spring Boot in 100 steps : beginner to expert - Karanam, Ranga; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2018)
"In this course, you will learn the features of Spring Boot and Spring Boot starter projects with a hands-on, step by step, approach to developing. You'll make a basic Todo management Java application using Spring Boot with Login and Logout functionalities, and basic REST service to manage survey questionnaire. You will be introduced to REST services, Spring security (authentication and authorization), Maven (dependencies management), Eclipse (IDE) and the Tomcat embedded web server. We will help you set up each one of these. You will learn about Spring Boot step by step in more than 100 steps."--Resource description page.
Title from resource description page (Safari, viewed April 18, 2018).
"In 28 minutes"--Title screen.
Presenter, Ranga Karanam.
Keywords: Spring (Software framework); Application program interfaces (Computer software); Application software -- Development; Electronic books